2000
DOI: 10.1006/jath.2000.3452
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Surjectivity

Abstract: We investigate the stability of surjective functions in Banach spaces. As a corollary to the main theorem we obtain a new stability result for isometries. Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Up to now the best known approximation estimates were 12ε + 5δ obtained by Dilworth [3, Prop. 2] and 2ε + 35δ obtained by J. Tabor [11]. The statement of our main result has also been known to be true under the additional condition that the set of points in X at which the norm is Fréchet differentiable is dense [3, Th.…”
Section: Introductionmentioning
confidence: 60%
“…Up to now the best known approximation estimates were 12ε + 5δ obtained by Dilworth [3, Prop. 2] and 2ε + 35δ obtained by J. Tabor [11]. The statement of our main result has also been known to be true under the additional condition that the set of points in X at which the norm is Fréchet differentiable is dense [3, Th.…”
Section: Introductionmentioning
confidence: 60%
“…The study of properties of non-surjective ε-isometries has been active since 90's of the last century (see, for instance, [1,3,[9][10][11][12][13]25,[27][28][29][30][31]). The question, if every standard ε-isometry f : X → Y admits a linear quasi-left inverse, that is, if there exists T ∈ B(Y f , X) so that T f − Id is uniformly bounded on X seems to be very natural.…”
Section: Introductionmentioning
confidence: 99%
“…Dilworth [6] showed that for every 𝛿surjective 𝜀-isometry mapping : f X Y → with f (0) = 0, where X and Y are Banach spaces, there exists an isometric mapping : U X Y → such that ( ) ( ) 12 5 f x U x  −  + . Then Tabor [23] changed this value to 2 35…”
Section:  mentioning
confidence: 99%